THE PATH TO WELL-BEING: MOTIVATIONAL FACTORS FOR TAKING UP MOUNTAIN BIKING IN THE CONTEXT OF THE COVID-19 PANDEMIC (Editora Impacto Científico, 2024)
The COVID-19 pandemic has profoundly changed physical activity habits, leading to the closure of traditional spaces and driving the search for outdoor alternatives. In this context, mountain biking (MTB) has stood out as a suitable practice, as it combines physical benefits, contact with nature, and a lower risk of crowding. The study analyzed motivational factors that led individuals from Penápolis, São Paulo, to take up MTB between March 2020 and 2021. The quantitative and descriptive research involved 28 beginner practitioners and used the Sports Activity Motivation Questionnaire (QMAD). The results indicated a predominance of males (62.7%), a varied age range, and socioeconomic diversity. Most participants were motivated by friends and practice MTB three times a week. Among the main factors identified were: physical fitness (62.5%), pleasure/occupation (60.7%), emotions (57.2%), and general affiliation (53.5%). On the other hand, competition (30.4%) and status (18.7%) were less relevant, suggesting a predominance of intrinsic motivation over extrinsic motivation. These results indicate that adherence to MTB during the pandemic was more related to health, well-being, and leisure than to competitive or social recognition factors. The study concludes that, even in smaller municipalities, MTB is an attractive, versatile sport that can contribute to both physical fitness and emotional health. For physical education professionals, understanding these factors is essential to encourage participation, maintain adherence, and strengthen the sport in the post-pandemic scenario.